Right heart remodeling in coronary heat disease: clinico-pathophysiological correlations - N. S. Buslenko; Yu. I. Buziashvili; I. V. Koksheneva; E. U. Asymbekova; O. M. Sherstyannikova (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To study right ventricular (RV) geometry and analyze clinico-pathophysiological processes, associated with right heart remodeling in coronary heart disease (CHD) patients. Material and methods. The study included 184 CHD patients, who underwent dobutamine stress echocardiography (EchoCG). Results. In CHD patients, structural and functional abnormalities of right heart chambers were registered: RV dilatation, dysconfiguration (increased ratio of RV transversal to longitudinal size), right atrium (RA) dilatation, tricuspidal valve fibrotic annulus distention, associated with tricuspidal insufficiency, and RF systolic function decrease. Among pathogenetic factors of right heart remodeling, there were: left heart function, mitral insufficiency, RV ischemic myocardial dysfunction, interventricular septum function. Conclusion.RV function determinants and right heart remodeling mechanisms are complex and multifactorial. This study analyzed regional RV geometry in various categories of CHD patients, and pathogenesis of right heart remodeling.